ANALYSIS OF POWER ASYMMETRY IN THE LEGISLATIVE PROCESS ANALYSIS OF THE WEAKENING ROLE OF THE HOUSE OF REPRESENTATIVES AS A LAWMAKER - Theresia, Louise; Asfia, Hilyatul; Juniar, Vindira Edka (LPPM STIH Putri Maharaja, 2025)
This study examines the phenomenon of power asymmetry between the executive and legislative branches in the legislative process in Indonesia after the amendment of the 1945 Constitution, which has resulted in the weakening of the role of the House of Representatives (DPR) as a lawmaker. The study aims to analyze the weakening of the DPR's position and the implications of power asymmetry on the quality of national legislation. The methods used are a juridical-normative and a juridical-empirical approach, with qualitative analysis of secondary data in the form of legislative documents, meeting minutes, and literature reviews. The study's results reveal two main findings. First, the DPR has been weakened since the amendment of the 1945 Constitution due to the executive's dominance in controlling the National Legislation Program (Prolegnas) agenda and party coalitions, with 91% of the 48 laws for the 2020-2024 period originating from executive initiatives, making the DPR more of a ratification mechanism than an independent lawmaker. Second, this asymmetry of power has serious implications for the quality of legislation, which lacks transparency and public participation, as seen in the case of the Job Creation Law, which was declared conditionally unconstitutional, and the high number of judicial reviews at the Constitutional Court (more than 1,700 petitions), which indicates a systemic failure of the legislative system. These findings emphasize the need to reformulate the roles and working mechanisms between the DPR and the President to ensure a more balanced, participatory, and accountable legislative process.